PEDAGOGICAL MANAGEMENT OF CREATION OF CONDITIONS, WAYS AND APPROACHES TO THE PERSONALITY OF A STUDENT OF PHYSICS (Pedagogy of Higher and Secondary Education, 2003)
This article deals with the pedagogical government in making conditions, approaches and ways to an individual of a pupil on materials of studying physics.